Fracture dislocation of the radial head: radial head excision or replacement - Yasin, N.F.; Singh, V.A. (2008)
A case of 28-year-old man with closed fracture dislocation of the radial head following a fall from height is reported. He was treated with radial head excision. The radial head is an important stabilizer of the elbow, thus the rationale of radial head excision in management of radial head fractures should be scrutinized. There is much debate regarding the optimal treatment for these fractures.